Predictors of job satisfaction among doctors, nurses and auxiliaries in Norwegian hospitals: relevance for micro unit culture - Veenstra Marijke; Hofoss Dag; Krogstad Unni; Hjortdahl Per (BMC, 2006)
Abstract Objective To explore what domains of work are important for job satisfaction among doctors, nurses and auxiliaries and to discuss differences between professional groups in the perspective of micro team culture. Design Cross-sectional survey data from hospital staff working clinically at inpatient hospital wards in Norway in 2000. Measures Linear regression models predicting job satisfaction for the three professions were compared. First, five domains of hospital work were examined for general job satisfaction. Based on the result of the first regression, five items concerning local leadership were explored in a second regression. Results A total of 1814 doctors, nurses and auxiliaries working at 11 Norwegian hospitals responded (overall response rate: 65%). The only domain of work that significantly predicted high job satisfaction important for all groups was positive evaluation of local leadership. Both steps of analyses suggested that professional development is most important for doctors. For registered nurses, experiencing support and feedback from the nearest superior was the main explanatory variable for job satisfaction. Job satisfaction of auxiliaries was equally predicted by professional development and local leadership. The results are discussed and interpreted as reflections of cultural values, loyalties and motivation. Conclusion The professional values of medicine, the organizational and holistic skills of nurses and the practical experience of auxiliaries should all be valued in the building of interdependent micro teams.